Sequential usage of diamond bur for CAD/CAM milling: Effect on the roughness, topography and fatigue strength of lithium disilicate glass ceramic - Madruga, Camila Ferreira Leite [UNESP]; Bueno, Mírian Galvão [UNESP]; Dal Piva, Amanda Maria de Oliveira [UNESP]; Prochnow, Catina; Pereira, Gabriel Kalil Rocha; Bottino, Marco Antonio [UNESP]; Valandro, Luiz Felipe; de Melo, Renata Marques [UNESP] (Elsevier, 2019)
The aim of this study was to evaluate the effect of sequential usage (milling order) of CAD/CAM diamond burs on the surface roughness, topography and fatigue performance of a lithium disilicate glass-ceramic. Seventy-two (72) ceramic discs (Ø= 13.5 mm; thickness= 1.2 mm; IPS e.max CAD) were milled using four pairs of burs and allocated into three groups (n = 24) according to the milling sequence: 1 through 6 (1−6), 7 through 12 (7−12), and 13 through 18 (13−18). The burs were evaluated under SEM at the different milling stages to depict any degradation generated by the milling sequence. Fatigue performance was assessed by a stepwise approach (initial strength of 20 MPa for 5000 cycles; incremental steps of 20 MPa for 20,000 cycles each until fracture; frequency of 20 Hz) using the ISO 6872:2015 recommendation for piston-on-three-balls biaxial flexure strength tests. Surface roughness, topography analysis and fractography of the failed discs were also performed. Survival analysis (Kaplan-Meier and Mantel-Cox post hoc test) showed that the milling sequence had no effect on the fatigue strength (190 – 201 MPa) or the number of cycles until fracture (174,958 – 180,087 cycles). Ceramic topography and roughness (Ra, Rz and RSm parameters) were similar among the groups, even though SEM analysis depicted CAD/CAM diamond burs degraded over time. Fractography evidenced all failures starting from surface defects introduced by milling at the samples’ tensile side. The sequential usage of CAD/CAM diamond burs (milling order) does not affect the lithium disilicate surface roughness, topography or fatigue performance.
Keywords: Fatigue. Machining. Flexural strength. Survival Analysis. Vitreous Ceramic